The financial statements and finance information in the governance of a joint stock company - Tabra Ochoa, Edison (2023)
The purpose of this paper is basically to give a study about the notions of ‘financial information’ and ‘financial statements’ from a corporate legal and accounting perspective. It includes definitions, characteristics, and effective use in the governance of a joint stock company.The results of this article essentially recommend for increase effective work of the shareholders assembly, board of directors, and CEO manager. And these suggestions may probably be included at the moment of the constitution of the company or in the modifications of its bylaws. With these ideas, we emphasize the importance of the integration corporate accounting and law.